Hedging against giants: Indonesia's strategy towards India and China in the Indian Ocean - Munabari, Fahlesa; Bulani, Diandri Filani; Ihsan, Rizky; Larasati, Nadia Utami (Political Science Program, Universitas Negeri Semarang, 2021)
China’s growing military and economic influence in the Indian Ocean has posed security challenges to India as a regional power in the region. As the two countries are competing over hegemony in the ocean, tensions grow and unavoidably create security uncertainties between countries in the region. Located strategically along major sea lanes connecting East Asia and South Asia, Indonesia has a strong interest in keeping the Indian Ocean safe and secure. However, the enduring India-China rivalry in the Indian Ocean has posed a threat not only to the Indonesia’s interest, but also the regional peace and security. This article analyzes how Indonesia as a middle power responds to these security uncertainties through hedging. This strategy is primarily aimed at mitigating risks Indonesia faces amid escalating tensions in the Indian Ocean. It is also geared towards avoiding conflict with target states —India and China. The article opens with an overview of the dynamics of India-China rivalry in the Indian Ocean. It then examines Indonesia’s hedging strategy towards India and China. It argues that Indonesia prefers to strengthen bilateral relations with India and China through increased cooperation in the maritime sector as part of this strategy. It demonstrates that while the Indonesia-India’s increased maritime cooperation is forged in the area of defense and security, Indonesia enhances engagement with China in the area of economic and infrastructure development.